Pengaruh Pendapatan Asli Daerah dan Dana Alokasi Khusus terhadap Belanja Daerah di Kota Banda Aceh - Fanny Nailufar; Sufitrayati Sufitrayati (Universitas Samudra, 2019)
The purpose of this study was to determine the effect of Local Revenue and Special Allocation Funds on Regional Expenditures in the city of Banda Aceh from 2010-2015. The data used in this study was secondary data, which was obtained from financial statements for the financial year ending on December 31, 2010 to 2015, which was obtained directly from the DPKAD of Banda Aceh City. The data analysis method used was multiple linear regression. The results of this study indicated that Regional Original Income and Special Allocation Funds simultaneously influence Regional Expenditures in the city of Banda Aceh in the period 2010-2015. Local revenue had a positive effect on regional expenditure with an influence of 306.4%. The special allocation funds had a positive effect on regional expenditure with an influence of 1365.6%. Suggestions for further research are expected to include other factors that are thought to influence regional spending such as general allocation funds. From the results of this study, it is expected that the Regional Original Revenues can increase, the government of the City of Banda Aceh is expected to increase the collection of Regional Taxes, Regional Retributions and other legitimate PAD (Original Local Government Revenue) intensively and actively up to a percentage of 100%.